Prognosis of bronchial asthma in children with different pulmonary function phenotypes: A real-world retrospective observational study - Liu, Lu; Ma, Hui; Yuan, Shuhua; Zhang, Jing; Wu, Jinhong; Dilimulati, Muheremu; Wang, Yahua; Shen, Shiyu; Zhang, Lei; Lin, Jilei; Yin, Yong (Frontiers in Pediatrics, 2023)
Objective: To follow up on the changes in pulmonary function phenotypes in children with asthma in the first year after diagnosis, and explore the risk factors of poor control in children with good treatment compliance. Methods: Children who were diagnosed with asthma in the Respiratory Department of Shanghai Children's Medical Center from January 1, 2019 to December 31, 2020 and were re-examined every 3 months after diagnosis for 1 year were continuously included, regardless of gender. We collected the clinical data, analyzed clinical characteristics of the different pulmonary function phenotypes at baseline and explored risk factors of poor asthma control after 1 year of standardized treatment. Results: A total of 142 children with asthma were included in this study, including 54 (38.0%) with normal pulmonary function phenotype (NPF), 75 (52.8%) with ventilation dysfunction phenotype (VD), and 13 (9.2%) with small airway dysfunction phenotype (SAD) in the baseline. Among them, there were statistically significant differences in all spirometry parameters, age, and course of disease before diagnosis (P < 0.05), and a negative correlation between age (r2 = -0.33, P < 0.001), course of disease before diagnosis (r2 = -0.23, P = 0.006) and FEV1/FVC. After 1-year follow-up, large airway function parameters and small airway function parameters were increased, fractional exhaled nitric oxide (FeNO) was decreased, the proportion of NPF was increased, the proportion of VD was decreased (P < 0.05), while there was no significant difference in the proportion of SAD. After 1 year of standardized treatment, 21 patients (14.8%) still had partly controlled or uncontrolled asthma. Our results showed that the more asthma attacks occurred within 1 year (OR = 6.249, 95%CI 1.711-22.818, P = 0.006), the more times SAD presented at baseline and Assessment 1-4 (OR = 3.092, 95%CI 1.222-7.825, P = 0.017), the higher the possibility of incomplete control of asthma. Conclusion: About 15% of the children with good treatment compliance were still not completely controlled after 1 year of treatment, which is closely associated with persistent small airway dysfunction.